2008
DOI: 10.1128/aem.02343-07
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in the Dynamics of Potentially Microcystin-Producing Strains in a Bloom-Forming Planktothrix agardhii (Cyanobacterium) Population

Abstract: The concentration of microcystins (MCs) produced during blooms depends on variations in both the proportion of strains containing the genes involved in MC production and the MC cell quota (the ratio between the MC concentration and the density of cells with the mcyA genotype) for toxic strains. In order to assess the dynamics of MC-producing and non-MC-producing strains and to identify the impact of environmental factors on the relative proportions of these two subpopulations, we performed a 2-year survey of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 59 publications
8
109
1
1
Order By: Relevance
“…The 'average' density-based P. rubescens cell quota determined in this study were in the range of other values reported in literature (Naselli-Flores et al, 2007;Briand et al, 2008;Kosol et al, 2009;Manganelli et al, 2010Manganelli et al, , 2016. Interestingly, the cell quota determined for M. botrys were constantly about 10 times higher than P. rubescens and in the range of Microcystis cell quota in the field estimated by Yu et al (2014) (0.001 and 1.326 pg cell -1 on the whole population and 0.012 and 1.876 pg cell -1 on the toxic cells).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The 'average' density-based P. rubescens cell quota determined in this study were in the range of other values reported in literature (Naselli-Flores et al, 2007;Briand et al, 2008;Kosol et al, 2009;Manganelli et al, 2010Manganelli et al, , 2016. Interestingly, the cell quota determined for M. botrys were constantly about 10 times higher than P. rubescens and in the range of Microcystis cell quota in the field estimated by Yu et al (2014) (0.001 and 1.326 pg cell -1 on the whole population and 0.012 and 1.876 pg cell -1 on the toxic cells).…”
Section: Discussionsupporting
confidence: 70%
“…The quantification of mcy genes of P. rubescens has been indicated as a better predictor of MC concentrations (Ostermaier and Kurmayer, 2010;Hautala et al, 2013). However, in this study the application of the linear regression to the mcyB + cells and MC reduced the percentage of MC variation explained, from >80% to ~50%, i.e., a value very close to what was observed by Briand et al (2008) in a population of P. agardhii and consistent with what we previously described in Lake Vico (Manganelli et al, 2016). There are several possible explanations for this outcome, as summarized in Kurmayer et al (2016), such as other coexisting non identified toxic species, problems in the amplification of mcy genes or mutation inactivating mcy genes.…”
Section: Discussionmentioning
confidence: 47%
“…There are many studies about cyanotoxins degradation, including microcystins produced by P. agardhii (Chen et al, 2008;Kormas and Lymperopoulou, 2013). However, besides its importance as a biomass producer and potentially toxic products (Briand et al, 2008;Tonk et al, 2005), almost no data can be found on the destination of DOC and how this process may affect the establishment and maintenance of the local bacterial community.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacterial blooms not only produce different kinds of toxins (microcystins, anatoxin-a, cylindrospermopsin, etc. ), but also synthesize and release odor compounds (2-methylisoborneol (2-MIB), Geosmin) (Briand et al, 2008;Graham et al, 2010;Wang et al, 2011). Among the water bloom forming cyanobacterial genera, Microcystis, Planktothrix, Dolichospermum (formerly as planktonic species in Anabaena genus) (Wacklin et al, 2009), and Aphanizomenon are usually the rulers governing the freshwaters and producing numerous bioactive secondary metabolites over the world (Pan et al, 2009;Vaitomaa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%